Headspace Gosford data: The local application of a National model. (August 2014) - Howe, Deborah; Coates, Dominiek; Batchelor, Samantha
Objectives: Despite the high prevalence of mental health problems for young Australians, many do not have ready access to treatment or are reluctant to seek help. Until recently there was a tendency for young Australians to fall between the gap of Child and Adolescent Mental Health Services and Adult Mental Health Services, and this has contributed to low rates of service use for young people. In 2006, the Australian Government sought to redress this gap in service delivery with its establishment of the Australian National Youth Mental Health Foundation, headspace. This paper presents demographic data collected at headspace Gosford over a 5.5-year period. Conclusions: The data presented indicates that headspace Gosford has been successful in improving early access to mental health treatment for young people on the Central Coast, in particular for young people aged 14–18. Headspace Gosford has attracted young people of both sexes, with a higher proportion of females. The majority of young people access headspace for mental health problems, predominantly depression and anxiety; however, a significant proportion report physical health or alcohol and drug-related reasons. The likelihood of these referral reasons is informed by gender and age.